2008
DOI: 10.1002/bmc.1131
|View full text |Cite
|
Sign up to set email alerts
|

LC‐MS analysis for the components captured by ECV304 cell from extract of Aconitum szechenyianum Gay.

Abstract: A novel method of cell affinity screening (CAS), cell affinity capture coupled with LC-MS analysis, was developed for screening the bioactive compounds related to cardiovascular diseases from the natural product libraries. One of the major characteristics lies in its function in affinity-capturing and separating the bioactive components from the natural product libraries in vitro. Another characteristic is its use in analyzing and identifying the target compounds, by employing high-performance liquid chromatog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…In a similar way, Ren et al adopted prostate cell membrane chromatography hyphenated with LC-MS to identify three bisbenzylisoquinoline alkaloids acting on ␣ 1A -adrenoceptor [110]. In addition, Yuan et al reported on a cell affinity capture coupled with LC-MS method for the screening of bioactive components of Aconitum szechenyianum [111]. Alkaloids of C. yanhusuo were screened to find potential aromatase binding agents using Reproduced with permission from [92].…”
Section: Alkaloidsmentioning
confidence: 99%
“…In a similar way, Ren et al adopted prostate cell membrane chromatography hyphenated with LC-MS to identify three bisbenzylisoquinoline alkaloids acting on ␣ 1A -adrenoceptor [110]. In addition, Yuan et al reported on a cell affinity capture coupled with LC-MS method for the screening of bioactive components of Aconitum szechenyianum [111]. Alkaloids of C. yanhusuo were screened to find potential aromatase binding agents using Reproduced with permission from [92].…”
Section: Alkaloidsmentioning
confidence: 99%
“…Jong et al [12] pres-ented an HPLC/MS methodology for the screening of ace-tylcholinesterase (AChE) inhibitors in a crude extract of Narcissus cv “Bridal Crown” bulbs. Yuan et al [13] cou-pled cell affinity screening (CAS) with HPLC/MS to screen the bioactive compounds related to cardiovascular diseases from the alkaloid extract derived from Aconitum szecheny-ianum Gay.…”
Section: Component Analysis Of Tcmsmentioning
confidence: 99%
“…C 19 - and C 20 -diterpenoid alkaloids possessing aconitine-type, 7,17-secoaconitine-type, and napeline-type skeletons, which are the main components of A . szechenyianum [ 2 , 3 , 4 , 5 ], possess anti-inflammatory, analgesic, anticancer, anti-epileptiform, and antiparasitic activities [ 6 , 7 , 8 ]. A. szechenyianum has been preliminarily studied; in that study, several norditerpenoid alkaloids were obtained with an aconitine or 7,17-secoaconitine skeleton, and these skeleton were demonstrated to have anti-inflammatory activities in a dose-dependent manner [ 9 ].…”
Section: Introductionmentioning
confidence: 99%